ChemInform Abstract: Knoevenagel‐Michael‐Cyclocondensation Tandem Reaction of Malononitrile, Various Aldehydes and Dimedone Catalyzed by Sulfonic Acid Functionalized Pyridinium Chloride as a New Ionic Liquid and Catalyst. Issue 39 (September 2015) - Zolfigol, Mohammad Ali; Khazaei, Ardeshir; Moosavi‐Zare, Ahmad Reza; Afsar, Javad; Khakyzadeh, Vahid; Khaledian, Omid
Abstract Sulfonic acid functionalized pyridinium chloride is prepared and used for the one‐pot synthesis of tetrahydrobenzo[b]pyran derivatives (IV) as a reusable catalyst under solvent‐free conditions.